Cracking of thick-walled fiber composites during bending tests. (June 2019) - Łagoda, Karolina; Kurek, Andrzej; Łagoda, Tadeusz; Błażejewski, Wojciech; Osiecki, Tomasz; Kroll, Lothar
Highlights: When normal stress is decisive for failure, crack begins on the surface of the specimen. When shear stress is decisive for failure, crack appears in the neutral plane at the boundary between tension and compression parts. The ratio of tensile to shear strength (X/S) of the composite is experimentally determined to be equal to 19.4. In the analysis of the three-point bending test, the Azzi-Tsai-Hill criterion is modified to obtain the value of equivalent stresses. Many criteria for composite materials do not allow comparison of the stress values determined through other criteria. Abstract: When formulating fracture criteria for fiber composites, it is essential to know the characteristics of the material's microstructure. The present research is carried out on specimens made of composite laminate with thermoplastic matrix PA6 reinforced by continuous glass fibers. Specimens are subjected to static three- and four – point bending tests at different spans between supports, resulting in different values of the ratio between maximal normal and shear stresses. Both distribution of normal stress coming from bending and distribution of shear stress, according to transverse shear stress in beams equation, coming from shear are considered. The results of the analysis are as follows: variation in the cross-section of shear stresses according to the transverse shear stress in beams equation, and distribution of bending stresses, according to the elastic model (value of normal stress increases linearly with increasing distance from the neutral plane). Depending on the combination of shear and normal stresses, cracking is initiated by either shear or normal stress.